Diversidade de Curculionidae (Scolytinae, Platypodinae) e Bostrichidae em plantios de teca, Tectona grandis L.f., 1782, no Estado do Pará, Brasil - Ferreira, Carla Samara dos Santos (2016)
The teak wood is one of the most valuable in the world, creating interest among producers in its quality and great commercial value. In Brazil plantations are concentrated in the Midwest and North, and due to the increase in these exotic plantations, monitoring is necessary to learn about their insect diversity. In 2008 a program to monitor the quarantine pest Sinoxylon unidentatum (Coleoptera: Bostrichidae) in Tectona grandis was started in the state of Pará, Brazil, because of the proximity to the state of Mato Grosso, area of occurrence of this pest. The general objective of this research was to monitor S. unidentatum and other beetle borers in Canaã dos Carajás, Cumaru do Norte, Pau D’ Arco, Rio Maria, São Domingos do Araguaia and Ulianópolis. Our specific objectives were to determine the richness and diversity of Curculionidae (Scolytinae, Platypodinae) and Bostrichidae in these plantations, and to know if there was a seasonal variation for their most abundant species. Trappings were done biweekly with ethanol-baited flight intercept traps from June 2011 to April 2013, totaling 115 collections. We captured 10147 specimens of beetle borers, distributed in eight sub-tribes, and totaling 90 species. In Rio Maria we found the greatest diversity of beetles and in São Domingos do Araguaia the greatest richness. There was a predominance of Scolytinae of the sub-tribe Cryphalina, which probably develop in the understory or dry material above the soil. We trapped significantly more Bostrichidae and Hypothenemus during the dry season. Sinoxylon unidentatum, target species that started this research, was not detected.